The Application of SOSA Bottle to Reduce The Pulmonary TB Transmission in Tanjung Gusta Penitentiary (Talenta Publisher Universitas Sumatera Utara, 2021)
The prevalence of pulmonary Tuberculosis (TB) in penitentiaries is 3 times higher compared to the general population. Reviono (2016), TB ranks in the 4th among the most common illnesses suffered by prisoners and is the major cause of morbidity and death in penitentiaries and detention centers in Indonesia. Sarumpaet and Syarifah (2018) posit the effectiveness of using SOSA (Sori-Syarifah) bags compared to SOSA bottles including 5% of Chlorophen accompanied by masks, tissues in cutting off the transmission of pulmonary TB with Acid Fast Bacilli (AFB+). SOSA bottles is significantly more effective (p <0.05) compared to the SOSA bags. A community service is needed in applying SOSA bottles to reduce the incidence of pulmonary TB, begins with the cooperation of partners, which is the doctor at the Penitentiary. The socialization of SOSA bottle application method has been carried out to reduce the risk of pulmonary TB transmission to the prison staff, health care workers, cadres and prisoner pulmonary TB patients at the penitentiary. The evaluation shows that the application of SOSA bottles has been done by the prisoner TB patients, while the reason for not using SOSA bottles is that there is no more sputum.